2017
DOI: 10.1016/j.carbon.2017.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a single sub-micron pore spanning a single crystal (100) diamond membrane and impact on particle translocation

Abstract: Julie V.. (2017) Fabrication of a single submicron pore spanning a single crystal (100) diamond membrane and impact on particle translocation. Carbon, 122. pp. 319-328.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 74 publications
(82 reference statements)
0
3
0
Order By: Relevance
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 circumference and rebound back, [28][29][30] which is also a failed translocation event. Because of the size variation of nanopipette nanopore, we investigated the changes of both ionic current and potential signals when different size NPs translocate through the same nanopore.…”
Section: Experimental Setup For Probing Dynamic Events Of Dielectric mentioning
confidence: 99%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 circumference and rebound back, [28][29][30] which is also a failed translocation event. Because of the size variation of nanopipette nanopore, we investigated the changes of both ionic current and potential signals when different size NPs translocate through the same nanopore.…”
Section: Experimental Setup For Probing Dynamic Events Of Dielectric mentioning
confidence: 99%
“…[25][26][27] The porosity of diamond crystals, lms, membranes and compacts can be achieved by a variety of methods. The most obvious top-down approach is based on post-growth treatment of solid micro-nanocrystalline diamond lms such as laser drilling, 25,28 reactive ion etching, [29][30][31] gas-mediated electron beam-induced etching, 32 and chemical etching of grain boundaries in nanocrystalline diamond lms. [33][34][35] A local etching of diamonds with catalytically active metals like Fe and Ni to pattern diamond lms and single crystals, particularly for hole formation, was used in a number of studies, [36][37][38][39][40][41][42] in which case, the treatment takes place in a hydrogen atmosphere at a temperature of about 900 °C.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the transport of counter‐ions can be facilitated in the ion channels because of the simultaneous improvements of their mobility and concentration therein 24,25 . Therefore, etching is a powerful technique for fabricating a large range of microstructures and nanostructures 26‐28 . According to the report, except a mass decrease, PANI was stable in 5 M H 2 SO 4 that no low‐molecular‐weight products were generated 29 .…”
Section: Introductionmentioning
confidence: 99%